Task-Specific Fatigue Among Older Primary Care Patients. (March 2017) - Romine, Perrin E.; Kiely, Dan K.; Holt, Nicole; Percac-Lima, Sanja; Leveille, Suzanne; Bean, Jonathan F.
Objective: Fatigue is a common condition contributing to disability among older patients. We studied self-reported task-specific fatigue and its relation with mobility task performance among community-dwelling primary care patients.Method: Cross-sectional analysis of baseline demographic and health data from a prospective cohort study of 430 primary care patients aged 65 years or older. Fatigue was measured using the Avlund Mobility–Tiredness Scale. Performance tasks included rising from a chair, walking 4 m, and climbing two flights of stairs.Results: Among demographic and health factors, pain was the only attribute consistently predictive of fatigue status. Self-reported chair rise fatigue and walking fatigue were associated with specific task performance. Stair climb fatigue was not associated with stair climb time.Discussion: Pain is strongly associated with fatigue while rising from a chair, walking indoors, and climbing stairs. This study supports the validity of self-reported chair rise fatigue and walking fatigue as individual test items.